2008
DOI: 10.2478/v10034-008-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and Non Small Cell Lung Cancer

Abstract: Non small cell lung cancer (NSCLC) accounts for approximately 80% of all lung cancers. Despite improvements in treatment protocols the survival rate in NSCLC remains poor. An improved understanding of cancer biology has led to the investigation of angiogenesis in NSCLC development and progression by intratumoral microvessel count or expression of angiogenic markers. The prognostic significance of several frequently assessed angiogenic factors and current antiangiogenic strategies which proved to be particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It has been experimentally revealed that sold tumors cannot grow beyond 1-2 mm in diameter without angiogenesis (Folkman, 1990). Tumor growth is dependent on the balance between increasing tumor-cell numbers through the proliferation of cells and decreasing numbers through an apoptotic process (Metodieva, 2008). If tumor angiogenesis is not sufficient, apoptotic cell death is accelerated the tumor growth is inhibited (Holmgren et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It has been experimentally revealed that sold tumors cannot grow beyond 1-2 mm in diameter without angiogenesis (Folkman, 1990). Tumor growth is dependent on the balance between increasing tumor-cell numbers through the proliferation of cells and decreasing numbers through an apoptotic process (Metodieva, 2008). If tumor angiogenesis is not sufficient, apoptotic cell death is accelerated the tumor growth is inhibited (Holmgren et al, 1995).…”
Section: Discussionmentioning
confidence: 99%